2000
DOI: 10.1046/j.1365-2281.2000.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Qi‐training on blood pressure, heart rate and respiration rate

Abstract: To examine the physiological effects of Korean traditional Qi-training, we investigated the changes in blood pressure, heart and respiratory rates before, during and after ChunDoSunBup (CDSB) Qi-training. Twelve normal healthy CDSB Qi-trainees (19-37 years old; trained for 1.3 +/- 0.2 years; 9 men and 3 women) volunteered to participate in this study. Heart rate, respiratory rate, systolic blood pressure and rate-pressure product were significantly decreased during Qi-training. From these results, we suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…These results are similar to those reported in other qigong studies. Many groups have assessed the effects of qigong on hypertensive patients and have reported that receiving qi positively affects BP, levels of catecholamines and cholesterol, heart rate, and other aspects of health (Agishi, 1998;Bornoroni et al, 1993;Lee et al, 2000bLee et al, , 2003Xing et al, 1993). BP has been directly linked to sympathetic nervous system (SNS) activity, and the urinary catecholamine assay has been used as an integrated measure of sympathoadrenal system activity (SSA)-a unique neuroendocrine unit comprising the sympathetic nervous system and the adrenal glands (Macdonald, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those reported in other qigong studies. Many groups have assessed the effects of qigong on hypertensive patients and have reported that receiving qi positively affects BP, levels of catecholamines and cholesterol, heart rate, and other aspects of health (Agishi, 1998;Bornoroni et al, 1993;Lee et al, 2000bLee et al, , 2003Xing et al, 1993). BP has been directly linked to sympathetic nervous system (SNS) activity, and the urinary catecholamine assay has been used as an integrated measure of sympathoadrenal system activity (SSA)-a unique neuroendocrine unit comprising the sympathetic nervous system and the adrenal glands (Macdonald, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized, controlled trial of diabetic adults in Japan, Tsujiuchi et al164 reported significant reductions in glycated hemoglobin and C-peptide in the qigong versus the usual care group. Likewise, uncontrolled studies conducted in China156,159 and Korea165 have demonstrated significant improvements in blood pressure,165 lipid profiles,156 and markers of insulin resistance and glucose tolerance 156,159. Similarly, a recent Hong Kong randomized, controlled trial of qigong in community-dwelling adults with mild hypertension demonstrated significant declines in body mass index, weight, and waist circumference that were comparable to those following a conventional exercise program.…”
Section: Qigong and Cvd Riskmentioning
confidence: 99%
“…111 It has been demonstrated that qigong can affect human physiology via the neuroendocrine system and thus help reduce pain, fatigue, and insomnia. 74,99,112 Researchers suggest that the upregulation of serotonin and ␤-endorphin levels after qigong practice may reflect the subjects' sense of increased calm and bliss. 102,113 The movements in qigong also stimulate the main acupoints and visceral channels of the body.…”
Section: Endorphin Theorymentioning
confidence: 99%